2015
DOI: 10.1094/cchem-04-14-0085-r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Functionality of Five Different Soybean Proteins in Hot‐Press Wheat Flour Tortillas

Abstract: Five different soybean protein sources were added to wheat flour to increase the protein content by 15–25%, and the resulting composite flours were optimally processed into hot‐press tortillas in a pilot plant. The rheological properties of composite flours were evaluated with the farinograph, alveograph, and other wheat quality tests. Tortilla‐making qualities of the control and soybean‐fortified flours were evaluated during dough handling, hot pressing, and baking. The resulting tortillas were tested in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Maize flour tortillas and wheat flour tortillas were manufactured with composite flours containing approximately 6.0% of defatted soybean meal with a protein dispersibility index (PDI) of 23.2±0.11, whereas the yeast-leavened table bread with a bread flour containing 4.5% soybean protein concentrate with a PDI of 52±0.5. The preparation and characteristics of these regular and soybean-fortified cereal-based foods are detailed by Chuck-Hernández et al, Perez-Carrillo et al, and Lazo-Velez et al ( 9 , 16 , 17 ). The regular and soybean-fortified products were dehydrated in a convention oven set at 50°C for 8 h and then ground in a Wiley mill equipped with a 2 mm sieve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maize flour tortillas and wheat flour tortillas were manufactured with composite flours containing approximately 6.0% of defatted soybean meal with a protein dispersibility index (PDI) of 23.2±0.11, whereas the yeast-leavened table bread with a bread flour containing 4.5% soybean protein concentrate with a PDI of 52±0.5. The preparation and characteristics of these regular and soybean-fortified cereal-based foods are detailed by Chuck-Hernández et al, Perez-Carrillo et al, and Lazo-Velez et al ( 9 , 16 , 17 ). The regular and soybean-fortified products were dehydrated in a convention oven set at 50°C for 8 h and then ground in a Wiley mill equipped with a 2 mm sieve.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that wheat bread, maize tortillas, and wheat flour tortillas can be successfully fortified with different soybean proteins without affecting sensory acceptance. These products contained 23–30% more protein compared to regular counterparts as well as an improved EAA score ( 9 , 16 , 17 ). To the best of our knowledge, there are no studies evaluating in vivo protein quality of soybean-fortified maize and wheat flour tortillas and bread at the same time.…”
mentioning
confidence: 99%
“…The addition of fats and oils also delays starch retrogradation, prolonging the shelf-life of the breads. On the other hand, the vegetal proteins modify the farinographic properties in a different way according to their type [ 82 , 83 ], but in general they reduce the strength of the doughs and their extensibility. The incorporation of fiber usually increases water absorption, the mixing tolerance and the tenacity of the doughs, but reduces extensibility [ 84 ].…”
Section: Dough Rheologymentioning
confidence: 99%
“…The enrichment or improvement of nutritional attributes of tortillas has focused in terms of protein, dietary fibre and or antioxidant capacity. Whole wheat-flour, oat:inulin mixes, whole and defatted soy flour, whole kamut flour, carrot juice, whole waxy barley, pinto bean flour, sprouted whole-wheat flour, sorghum polyphenols, distillers dried grains with solubles are some ingredients previously evaluated in tortilla (Scazzina et al 2008;Anton et al 2009;Prasopsunwattana et al 2009;Barros et al 2010;Heredia-Olea et al 2015;Pourafsar et al 2015;Liu et al 2017;Perez-Carrillo et al 2015;Serna-Saldivar 2016). In all cases, the challenge is to retain tortilla quality attributes like colour, texture and organoleptic acceptance.…”
Section: Introductionmentioning
confidence: 99%